Between venture and consolidation. Conditional opportunism of Italian mafia clans in Europe (Rivista di Studi e Ricerche sulla criminalità organizzata, 2021)
This article presents a preliminary analysis of data collected on 6 European countries - Germany, Switzerland, the Netherlands, Belgium, Spain, and Romania - to trace the evidence of the mobility of Italian mafia clans. In between venture and consolidation of activity, Italian mafias abroad remain anchored to the logic of opportunism more than strategy. The success of such opportunism is conditioned by different factors linked both to the nature of groups and their conditions of origin, as well as their territories of destination.
Keywords: mafia mobility; mafia; ‘ndrangheta; camorra; Italian mafia; Europe